2021
DOI: 10.1111/rec.13404
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and population structure of transplanted Aristida beyrichiana (wiregrass) tussocks: results of a 37‐year study

Abstract: Aristida beyrichiana (wiregrass) is a foundation bunchgrass species in many southeastern U.S. native pine communities, but it has been dramatically reduced in extent. The potential for reintroduced wiregrass to reproduce and spread is not well studied because of its slow growth and limited conditions for successful reproduction. We present a case study where tussocks of wiregrass were transplanted and recensused 18 and 37 years later to study their population dynamics. We remeasured a subset of tussocks to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
(83 reference statements)
1
0
0
Order By: Relevance
“…Also, we have observed that most of these are masting species, producing abundant fruit and seeds only in certain years, thus limiting opportunities for establishment. The lack of A. beyrichiana , the dominant perennial grass in the undisturbed sites, is consistent with many soil disturbance studies documenting its limited dispersal capacity, low seed viability, and requirement for late spring or summer fires to flower (Laucevicius et al, 2021; Mulligan et al, 2002; Perez, 2014). Other species that were absent or greatly underrepresented in the repeated‐disturbance plots compared with undisturbed plots included Ceanothus americanus L., Eupatorium album L., Malus angustifolia (Aiton) Michx., Mimosa quadrivalvis L., Pteridium pseudocaudatum (Clute) Christenhusz., Sericocarpus tortifolius (Michx.)…”
Section: Discussionsupporting
confidence: 81%
“…Also, we have observed that most of these are masting species, producing abundant fruit and seeds only in certain years, thus limiting opportunities for establishment. The lack of A. beyrichiana , the dominant perennial grass in the undisturbed sites, is consistent with many soil disturbance studies documenting its limited dispersal capacity, low seed viability, and requirement for late spring or summer fires to flower (Laucevicius et al, 2021; Mulligan et al, 2002; Perez, 2014). Other species that were absent or greatly underrepresented in the repeated‐disturbance plots compared with undisturbed plots included Ceanothus americanus L., Eupatorium album L., Malus angustifolia (Aiton) Michx., Mimosa quadrivalvis L., Pteridium pseudocaudatum (Clute) Christenhusz., Sericocarpus tortifolius (Michx.)…”
Section: Discussionsupporting
confidence: 81%